Low prevalence of metallo-beta-lactamase in Pseudomonas aeruginosa isolated from a tertiary burn care center in Tehran. (September 2015) - Lari, Abdolaziz Rastegar; Azimi, Leila; Soroush, Setareh; Taherikalani, Morovat
Production of metallo-beta-lactamase (MBL) is one of the main mechanisms for resistance in carbapenem antibiotics. Detection of MBL-producer Pseudomonas aeruginosa is crucial in preventing its spread to other gram-negative bacteria. The aim of this study was to evaluate combination disc (CD) for identification of MBL-producer P. aeruginosa by polymerase chain reaction (PCR). A total of 255 imipenem resistant P. aeruginosa were collected from burn patients. Antibiotic susceptibility testing was conducted after purification and identification. Double-disc synergy test (DDST) with EDTA and combination disc test (CDT) with dipicolinic acid were performed for phenotypic detection of MBL and the PCR was carried out for blaVIM, blaIMP, blaNDM-1, blaSPM-1 genes. DDST with EDTA was negative in all cases, but 161 isolates were positive in CDT with dipicolinic acid. Further, blaVIM and blaIMP were detected in five and four strains, respectively. None of the isolates were positive for BlaNDM-1 and blaSPM-1 . The results of this study showed that the prevalence of MBL is low in imipenem resistance P. aeruginosa and that other mechanisms could be involved in resistance to imipenem in this bacterium.